1996
DOI: 10.1177/089198879600900308
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Late-Onset Psychosis: Integrating Neuropsychological and SPECT Data

Abstract: We report the case of a 67-year-old woman who experienced a sudden onset of psychotic illness (i.e., prominent delusions and hallucinations) that has endured for approximately 3 years. As part of her neurobehavioral work-up, a SPECT scan revealed right frontal and left anterior temporal-lobe hypoperfusion. Serial neuropsychological evaluations obtained 2 years apart demonstrated a steady decline on tests of executive control (monitoring, allocation of attention, perseveration) and visuospatial abilities, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Brain asymmetry within the delusional group was on par with that of normal aging, while those AD patients without delusions showed a relative lack of asymmetry. Cloud et al (1996) found the same pattern of atrophy in a case study of an unusual LOS woman showing phantom boarder syndrome and delusions of suspicion. Their subject showed longstanding delusions of suspicion changing to phantom boarder syndrome after an attempted burglary and progressive executive functioning.…”
Section: Neuropsychological Features and Neuroanatomic Considerationsmentioning
confidence: 61%
“…Brain asymmetry within the delusional group was on par with that of normal aging, while those AD patients without delusions showed a relative lack of asymmetry. Cloud et al (1996) found the same pattern of atrophy in a case study of an unusual LOS woman showing phantom boarder syndrome and delusions of suspicion. Their subject showed longstanding delusions of suspicion changing to phantom boarder syndrome after an attempted burglary and progressive executive functioning.…”
Section: Neuropsychological Features and Neuroanatomic Considerationsmentioning
confidence: 61%
“…A high incidence of Lewy body dementia and argyrophilic grain disease pathology, including deterioration of the frontal and temporal lobes have also been detected in VLOSLP patients (Cloud et al . 1996; Nagao et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One pathological study has associated VLOSLP with ventricular enlargement, generalised atrophy and vascular brain damage (Antonova et al 2004). A high incidence of Lewy body dementia and argyrophilic grain disease pathology, including deterioration of the frontal and temporal lobes have also been detected in VLOSLP patients (Cloud et al 1996;Nagao et al 2014). As Lewy body dementia is also associated with symptoms such as delusions and hallucinations, research comparing VLOSLP with these conditions, perhaps with the aid of neuroimaging or neuropathological data, could be helpful in improving differential diagnosis and understanding pathophysiology.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…To date there are few SPECT studies of a case with psychotic symptoms (e.g. fronto‐temporal degeneration, 11 schizophrenia 5,6 and late‐onset psychosis 12 ). All of these studies demonstrate hypoperfusion in the temporal lobe as our case does.…”
Section: Discussionmentioning
confidence: 99%